2018
DOI: 10.3389/fchem.2018.00219
|View full text |Cite
|
Sign up to set email alerts
|

High Efficient Visible-Light Photocatalytic Performance of Cu/ZnO/rGO Nanocomposite for Decomposing of Aqueous Ammonia and Treatment of Domestic Wastewater

Abstract: Photocatalytic removal of ammonium-nitrogen (NH4+-N) from water using solar energy is an approach of high interest and applicability due to the convenience in application. ZnO has a great potential in photocatalytic decomposition of NH4+-N and conversion of this nutrient to under visible light irradiations. However the applicability of pristine ZnO though is limited due to its reduced capacity to utilize light from natural light. Herein, we report a two-step ZnO-modified strategy (Cu-doped ZnO nanoparticles, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…Cu is frequently used as a doping transition metal to develop ZnO NPs with improved properties for advanced applications. Indeed, Cu atoms can substitute Zn in the ZnO lattice structure thanks to their identical valence state and similar ionic radii [ 18 ]. In addition, Cu has a large ionization energy and low formation energy, which speeds up the integration of Cu into the ZnO lattice [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu is frequently used as a doping transition metal to develop ZnO NPs with improved properties for advanced applications. Indeed, Cu atoms can substitute Zn in the ZnO lattice structure thanks to their identical valence state and similar ionic radii [ 18 ]. In addition, Cu has a large ionization energy and low formation energy, which speeds up the integration of Cu into the ZnO lattice [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite quite similar radii for Cu 2+ and Zn 2+ cations (Cu 2+ : 0.73 Å, Zn 2+ : 0.74 Å) [ 18 ], relatively low values of Cu content can be incorporated in the ZnO wurtzite structure, without the phases demixing. In the case of Cu-doped ZnO nanorods synthesized using an ice-bath-assisted sonochemical technique, Othman et al [ 21 ] reported a single phase (wurtzite) up to a doping content of 4% Cu.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the shortage in water supply worldwide and improving the environmental pollution, the elimination of several impurities from adequate water has major pervasive problem worldwide with widespread concerned. Nowadays the rapid industrialization of modern society exclusively in the developing countries, organic dyes are widely used in paper, leather, textile, pigment, cosmetic, food, and drug manufacturing [1][2][3]. Besides, the industrial and sanitary sewage comprises dyes cause water contamination as serious health problems and they are hazardous effects toward aquatic organisms, plants, humans, animals and aquatic ecosystem.…”
Section: Introductionmentioning
confidence: 99%
“…Different mono-component metal oxide photocatalyst such as ZnO (He et al, 2018;Smazna et al, 2019), TiO 2 (Andronic et al, 2014;Castellanos et al, 2020), WO 3 (Yang et al, 2018;Zhao et al, 2020) or SnO 2 (Enesca et al, 2012a;Patil et al, 2018) were widely used for wastewater and air pollutant removal. Although efficient, these materials have limitations in terms of charge carrier recombination, absorption range, and photoactive crystalline structure.…”
Section: Introductionmentioning
confidence: 99%